South African Heart Association newsletter - Spring 2013 - Snyders, Adriaan (SA Heart Journal, 2017)
In this last Newsletter for 2013 you will have the opportunity to see what our SIGSs and the Standing Committees of SA Heart have been busy with during 2013 and plan for 2014, all for the benefit of Cardiology Care in South Africa and the Members of SA Heart. I applaud these members who, without any remuneration and often without other forms of recognition, spend many hours and at times even their own finances to lead and/or participate in these projects. They need your support and involvement.